Seed germination of forestry species - Reis, Geraldo Gonçalves dos; Brune, Arno; Rena, Alemar Braga (Pesquisa Agropecuaria Brasileira, 2014)
The seed germination of 32 forestry species was studied in germinator, (30°C, in the obscurity) and/or in seedbed. Most of them were harvested in the 1974/75 period and conditioned in laboratory environment or in cold chamber (2-5°C) with forced ventilation until testing time, in 13.8.75. Thirteen species did not germinate, and their seeds deteriorated during the test; three others neither germinated nor deteriorated, probably because they were dormant; seven others germinated at the rate of less than 15% and presented germinative energies less than 1.0; six others showed germination higher than 40% and germinative energies less than 2.0, and completed the germination in more than 90 days; the three remainder species attained germination percentage and germinative energies higher than 50% and 7.0, respectively. These species completed their germination sooner than 30 days. The results suggested that 18 species have some mechanism of dormancy controlling the germination of the seeds.